'Disjointed days': Contemporary art and the human right to housing. (1st October 2016) - Marquis, Vincent
The human right to housing has a strange status in law, simultaneously codified in a number of international conventions and severely criticized, misunderstood or misinterpreted. This article considers two artistic views on the value of the human right to housing: Martha Rosler's 'If You Lived Here...' and Casco's recent projects on housing, gentrification and squatting, including the sitcom Our Autonomous Life? and the Convention on the Use of Space. I argue that examining the particular social contexts and the specific content of the claims made by these artists – notably the importance of housing to privacy, autonomy and freedom – illuminates a promising path forward for the right's legal interpretation and protection.